Hesburgh of Notre Dame Assessments of a Legacy - Ream, Todd C.; James, Michael J. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This book is not just about the legacy of Fr. Hesburgh, but also about the future of American Catholicism." -Massimo Faggioli, Professor of Historical Theology, Villanova University, USA "A stimulating and revealing set of essays on one of the most important Catholic figures of the American twentieth century." -John T. McGreevy, Provost and Professor of History, University of Notre Dame, USA "Hesburgh can justifiably be remembered as American higher education's 'Man for All Seasons'." -John R. Thelin, University Research Professor, University of Kentucky, USA "Todd Ream and Michael James provide a fresh look at the audacious and spirited leadership of one of the most influential university presidents in our nation's history." -Linda M. LeMura, President, LeMoyne College This volume is the first comprehensive assessment of the life and legacy of FatherTheodore Hesburgh (1917-2015), an educator, priest, public servant, and long-serving President of the University of Notre Dame. Despite being a transformative figure in Catholic higher education who led the University of Notre Dame for 35 years and wielded influence with US presidents on civil rights and other charged issues of his era, secular accounts of history often neglect to assess the efforts of religious figures such as Hesburgh. In this volume, the editors and their authors turn a fair-minded but critical eye to the priest's record to evaluate where he fits into the long development of Catholic higher education and Catholics' role in American public life. Todd C. Ream serves on the higher education and honors faculties at Taylor University, USA, as a senior fellow for the Council for Christian Colleges and Universities and the Lumen Research Institute, and as the publisher for Christian Scholar's Review. Michael J. James serves on the higher education faculty and as the Director of the Institute for Administrators in Catholic Higher Education at Boston College, USA. .
Chapter 1. Introduction -- Chapter 2. The Church -- Chapter 3. The University -- Chapter 4. Science and Technology -- Chapter 5. Civil and Human Rights -- Chapter 6. Foreign Relations and Peace -- Chapter 7. Service -- Chapter 8. Intercollegiate Athletics -- Chapter 9. Leadership -- Chapter 10. Conclusion. .
Keywords: Educational sociology; School management and organization; School administration; Education, Higher; Religion; Sociology of Education; Organization and Leadership; Higher Education; Religion